Individualism and Nationalism: Negotiating Identity through Sports in Tony Adams Addicted - ZEROUALA, Louai abdsalam; CHERAIFIA, Djihed (Faculty of Letters and Foreign Languages Department of English, 2025)
Sports narratives are seen as tales of national symbolism where individuals manifest their nationalism and display their national identity. Collective sports narratives, in particular, value the collective aspect of individuals working as a team to represent their nation at the expense of their individualism and selfhood in private. In the era of postmodernism, sports narratives are seen as tales of the erasure of the self and individualism, where athletes lose themselves to serve their team and their nation. This dissertation provides a psychoanalytical analysis of Addicted by Tony Addams, an autobiography that follows novelistic conventions as a sports narrative. It professes that the focus on nationalism and national identity in the novel creates the conditions for self-discovery, fostering both personal identity and individual autonomy. Addicted by Tony Adams offers a new perspective as a sports narrative whereby nationalism and national identity does not diminish individualism and the search for personal identity but rather foster it. In this context, nationalism functions analogously to Lacan’s mirror stage: it reflects individualism and encourages the search for personal identity, particularly within sports narratives. This dissertation aims to demonstrate, while approaching Addicted through Lacanian psychoanalysis and the theoretical framework of postmodern literature, that despite its overwhelming support of nationalism and national identity, sports narratives advocate for individualism and the search for the self on a personal level. It situates Tony Adams’ Addicted within the context of postmodern literary analysis, highlighting its use of narrative fragmentation, self-reflection, and the tension between nationalism and individual identity. It focuses on a psychoanalytic reading of Tony Adams’ autobiographical narrative.